Repositioning the Criminal Policy on Doxing as a Criminal Act in Indonesia - Rafid Ihsan Lubis; Patricia Audrey Ruslijanto; Bambang Sugiri (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Under Indonesian law, there are no specific regulations governing the criminal offense of doxing. The criminal act of doxing is categorized as a violation of personal data, which is linked to the Personal Data Protection Act (PDP Act) and the Electronic Information and Transactions Act (ITE Act). Given this situation, this study was conducted with the aim of identifying and analyzing the criminal law policy regarding the formulation of the criminal act of doxing, as well as to identify and analyze the fulfillment of the criminalization parameters for the criminal act of doxing and the prospects for its regulation in the future. The research method employed is a normative legal approach, utilizing legislative analysis, conceptual analysis, philosophical analysis, and casuistic analysis. The data used in this legal research consists of secondary data, comprising primary, secondary, and tertiary legal materials. The findings of this thesis indicate that criminal law policies in defining the criminal offense of doxing must be examined from philosophical, sociological, historical, and comparative perspectives. In its formulation, the aim must be to create effective policies that focus not only on enforcement but also on prevention and rehabilitation. Furthermore, in its implementation, this policy must remain adaptable to the evolving times. Another finding of the study concerns the criminal act of doxing, which can be interpreted as an act that does not yet meet the parameters of criminalization—namely, legality, subsidiarity, and equality before the law. Based on this, the criminal act of doxing can be categorized as an offense requiring separate regulation. The formulation of the criminal offense and the sanctions that may be imposed must meet the criteria for criminalization. The criteria for criminalization must be used to assess the extent of the success of the formulation of criminal acts and the corresponding criminal sanctions to be established.